An alternative IT investment framework based on university learning model in asset management - Thananchana A. (2017)
Copyright © 2017 Inderscience Enterprises Ltd. Ideally with no constraints on the budget, an investment in information technology should be easy and straightforward. Conventional method for the IT investment is adapted from the existing financial techniques which focus mainly on the returns from the assets invested. However, due to specific natures of an IT asset, financial techniques may become inappropriate and misleading. This paper proposes an alternative investment framework for the information technology assets by utilising the experiences of experts since its installation. To utilise these experiences in the proposed investment framework, the learning curve is constructed and represents as the organisational learning model in costs, performance and risks according to the asset management framework. College of Arts, Media and Technology within Chiang Mai University is used as the case study. The results have shown that the alternative investment framework performs better than conventional evaluation methods and leads to the most suitable investment option.